Seismic Performance of Cfrp Jacketed Sub-Standard Rc Columns Under High Axial Stress and Shear Demand - Demir, Merve Nur; Demir, Uğur; Demir, Uğur; Demir, Cem; İlki, Alper (Springer, 2022)
In the last decades, lessons learnt from the major earthquakes, that occurred in many countries, brought revisions in prevailing seismic design codes. As a consequence of this phenomenon, the current building stock in Turkey is mainly comprised of reinforced concrete (RC) buildings which were designed according to different seismic design codes. The presented paper is a component of a comprehensive investigation which containing three variables i) high axial load ratio defined as axial load divided by the axial capacity, ii) high shear demand defined as the ratio of shear demand at flexural yielding to shear resistance and iii) low transverse reinforcement ratio owing to large spacing among steel reinforcements. Thus, a total of four full-scale square RC columns comprised of i) one column designed to comply with the former Turkish Seismic Design Code (TSDC, 1975) and ii) three columns which are not compliant to any design codes (referred as sub-standard), were tested under high axial load ratio, 0.4 for code-conforming and 0.75 for sub-standard columns, combined with reversed cyclic lateral loading. The columns were also designed to have high shear demand in the order of 0.62 and 0.80 for bare sub-standard according to ACI 318 (2019) and TBEC (2018) design codes as sometimes observed in existing sub-standard structures. In addition to that, the ratio of shear demand for the code-conforming column is calculated 0.43 and 0.50 as per design codes, respectively. Besides, the ratio of transverse reinforcement area to the minimum required transverse reinforcement area was 0.19 and 0.77 for sub-standard columns according to ACI 318 (2019) and TBEC (2018), respectively. For the code-conforming column, the aforementioned ratio was 0.57 and 1.32 for both design codes, in the same manner. One of the sub-standard columns was kept as a reference column while the other two of them have been externally jacketed with one layer or two layers of carbon fiber-reinforced polymer (CFRP) sheets. Test results pointed out that the confinement provided by CFRP jacketing has remarkably improved the performance of seismically-deficient RC columns subjected to high axial compression under high shear demand in terms of lateral load capacity and ductility. The experimental results were also supplemented with theoretical work to evaluate the effects of CFRP jacketing on the seismic behavior of sub-standard RC columns.
Keywords: CFRP; Column; Retrofitting; Seismic performance